Critical pause: Athletes` stories of lockdown during COVID-19 - Whitcomb-Khan, G.; Wadsworth, N.; McGinty-Minister, K.; Bicker, S.; Swettenham, L.; Tod, D. (The Sport Psychologist, 2021)
This study explored the experiences of elite athletes during the initial stages of lockdown as a result of the COVID-19 pandemic. The eight recruited participants (three females, five males) were asked to tell a story of their lockdown experience. Narrative analysis was used to explore the athletes` stories. The athletes` narrative is best represented in four distinct sections: a) Threat to Goals, b) On-Going Consequences, c) Overcoming COVID-19, and d) Adapting to COVID-19. Four narrative themes were also co-constructed from the athletes` stories: a) Factors Athletes Found Challenging, b) Loss, c) Strategies that Benefitted Athletes Psychologically, and d) Silver Linings. Combined, these findings suggest that the initial stages of lockdown are best described as a critical pause. We present applied implications for athletes and sport psychology practitioners. We also recommend future research investigate the longitudinal effect of prolonged lockdown on athletes` lives and a potential return to sport.